(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2023)
Thickening compositions of a new composition have been developed for printing mixed fabrics based on cotton and nitron fibers. The influence of the components of thickening compositions on the rheological properties of the composition depending on their concentration was studied. The development of a new composition of the thickening composition, its physicochemical and rheological properties, has been established.